Comparative evaluation of three gingival displacement materials for efficacy in tissue management and dimensional accuracy - Vijeta Gajbhiye; Rajlakshmi Banerjee; Priti Jaiswal; Anuj Chandak; Usha Radke (Wolters Kluwer Medknow Publications, 2019)
Aim: Displacement of gingiva is essential for obtaining accurate impressions for the fabrication of fixed prostheses, particularly when the finish line is at or within the gingival sulcus. Various newer impression materials have been introduced to achieve gingival displacement while recording the impressions. A comparative evaluation of these new gingival displacement materials was deemed necessary for efficacy in tissue management and dimensional accuracy. Materials and Methods: Ten individuals were selected according to the inclusion and exclusion criteria for gingival displacement using retraction cord impregnated with aluminum chloride and two polyvinyl siloxane impression materials (Aquasil and NoCord VPS impression system) according to Latin block design. Intraoral scanner and Vernier caliper were used to study and compare the dimensional accuracy of each die obtained following which the dies were sectioned and evaluated under optical microscope with image analyzer to measure the amount of gingival retraction. Results and Conclusion: Statistical analysis showed that the amount of gingival retraction obtained by using retraction cord impregnated with aluminum chloride as gingival retraction agent was maximum as compared to NoCord followed by Aquasil. All three gingival displacement techniques could produce gingival displacement >0.2 mm which is the optimum amount of retraction required for impression making. All the three materials are found to be dimensionally accurate.